2018
DOI: 10.1002/cncr.31408
|View full text |Cite
|
Sign up to set email alerts
|

The impact of BCR‐ABL1 transcript type on tyrosine kinase inhibitor responses and outcomes in patients with chronic myeloid leukemia

Abstract: Although the majority of patients with chronic myeloid leukemia do well with treatment with tyrosine kinase inhibitors (TKIs), some patients still have inferior outcomes. There are many factors that might play a part, including the different BCR-ABL1 transcript types at baseline. The current study was performed to determine the possible impact of different transcripts on the treatment responses and outcomes of patients with chronic myeloid leukemia who are receiving TKI therapy. The authors performed a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 56 publications
3
21
0
Order By: Relevance
“…The presence of e14a2 at baseline was associated with higher molecular response rates to imatinib. [17][18][19][20] While some studies have demonstrated a trend toward better survival outcomes with e14a2 transcript, 18,19 in other studies the type of transcript did not have any significant impact on long-term survival outcomes. 17,21 There are very limited data regarding the impact of these transcripts on response to second-generation TKI therapy.…”
Section: Bcr-abl1 Transcript Variants In CMLmentioning
confidence: 87%
“…The presence of e14a2 at baseline was associated with higher molecular response rates to imatinib. [17][18][19][20] While some studies have demonstrated a trend toward better survival outcomes with e14a2 transcript, 18,19 in other studies the type of transcript did not have any significant impact on long-term survival outcomes. 17,21 There are very limited data regarding the impact of these transcripts on response to second-generation TKI therapy.…”
Section: Bcr-abl1 Transcript Variants In CMLmentioning
confidence: 87%
“…Previous studies suggested that imatinib treatment was associated with a DMR and a favorable outcome in patients that expressed the e14a2 transcript. 5 These results were confirmed by a study with imatinib or second-generation TKI used frontline, showing that the achievement of a stable DMR was 63.8% in e14a2 expressing group compared with 36.2% in the e13a2 group. 6 Preliminary data involving a large cohort of CML patients treated with nilotinib in several clinical trials, showed no significant differences in PFS (88% vs 93%) and OS (89% vs 94%) between the e13a2 and e14a2 groups.…”
mentioning
confidence: 63%
“…4,6 Similarly, in the TKI era, response to TKI treatment is excellent in patients with TR-CML in chronic phase. 6,11 Iriyama et al 6 have investigated the prognosis of 297 de novo CML and 11 TR-CML patients with a median follow-up of 48 months. Primary malignancy was solid tumor in 10 patients, while it was acute lymphoblastic leukemia in one patient.…”
Section: Discussionmentioning
confidence: 99%